Deviation Analysis of Processed Tooth Profile with Plated CBN Hard Gear Honing - Yun Yan; Mandong Zhang (Jixie chuandong)
Plating CBN hard gear honing processing gear with standard involute， the general vicinity of the workpiece tooth pitch will be a “mid concave” error. The Pro/E software is used to establish three-dimensional parameterization entity model of gear-honing-tools and gears， and build meshing assemble between them accurately. ANSYS software is used to simulate the contact analysis of plating CBN hard honing process. Through the analysis of the contact stress of the tooth surface and the normal deformation of the processed tooth surface， the influence factors on the concave error are found out. Then，under the premise of other parameters are fixed， the tooth numbers of gears is changed respectively， comparing the change of contact stress， and then the influence of the teeth numbers to on “mid concave” error is found out.